Systematic Review of Studies on Science and Technology in Iran - Mahroyan, Nazanin; Mehraein, Mostafa; Navabakhsh, Mehrdad (Journal of Assessment and Research in Applied Counseling (JARAC), 2021)
Background and Aim: While research literature related to science and technology tends to be immersed in presenting thin and thick descriptions of these two issues, this research aims to study and categorize the works of intellectuals who have addressed the issue of science and their approach to it. Methods: In this study, to identify and analyze the main aspects of the social conditions in which Iranian intellectuals’ understanding and perception of science and technology have emerged, and their various discourses on science and technology have been formed, we adopted a sociolinguistic-semiotic perspective. Results: Throughout modern history, we have encountered various approaches and opinions from Iranian intellectuals regarding the issue of science and how to address it. To study and research in this collection of opinions, we strive to categorize them into different research categories by examining research and studies conducted in the field of "science, technology, and higher education" and presenting an exploratory image of them and showing the relationships between them. We did this by constructing a formal analytical model based on abstract theories in cultural sociology, cultural studies, semiotic theories, postcolonial studies, and literary criticism. In this article, we identified the research literature related to science and technology and categorized them based on the method or analytical strategy of each research within different research categories. Conclusion: In this article, we have shown how social events and phenomena such as the decline of the Qajar government and its collapse, the collapse of traditional religious order, the disruption of the cultural order of Iranian society from the early twentieth century to the present, the country’s need for development and modernization, facing disasters and natural events such as famine and contagious diseases, a strong military, a modern education system, educated forces to take over the bureaucratic system of the country, and so on, gradually turned the issue of science and technology into one of the most important indices and questions of the ideological discourses existing in the intellectual space of the country and led to debates and intellectual discussions on this matter.